DAMPAK COVID-19 TERHADAP HARGA SAHAM DAN VOLUME PERDAGANGAN PT GARUDA INDONESIA, TBK - Indri Ayu Tansar; Tri Ningsih (STMIK Mardira Indonesia, Bandung, 2021)
This research aims to know the capital market reaction, especially stock prices and trade volume due to pandemic covid-19 (case study in PT Garuda Indonesia Tbk). The data used in this research was secondary in closing price and volume trading PT Garuda Indonesia Tbk. This research data takes 31 days before and 31 days after announcing the first case of Covid-19 in Indonesia. The analytical technique used in this study is the Paired Sample T-Test. The study results stated a significant difference in stock prices before and after the national announcement of the first covid-19 case in Indonesia; this difference was proven by the p-value = 0.000 with t count = 17.924, which was more significant than t table = 1.96. Meanwhile, the trading volume did not significantly differ before and after the national announcement of the first COVID-19 case in Indonesia, as seen from the p-value = 0.964 with t count = 0.045, which is smaller than t table = 1.96. The results of this study expect to contribute to company managers in making investment decisions by taking into account the influence of the condition of the aviation industry in Indonesia and is expected to help investors minimize losses that investors may suffer due to uncertain conditions during the pandemic. Keywords : Stock Prices, Trade Volume, Covid-19.